Nb-Compact and Nb-Lindelöf Spaces - Ali, Haider Jebur; Naief, Anas Mohammed Saeed (Iraqi Journal of Science, 2023)
In this work, we present new types of compact and Lindelöf spaces and some facts and results related to them. There are also types of compact and Lindelöf functions and the relationship between them has been investigated. Further, we have present some properties and results related to them.